Electric storage device

By using positive electrode active material particles with an internal void ratio of less than 15% and graphite particles with an internal void ratio of less than 2%, combined with the pressing state of the electrode body, the problem of the power input of the power storage element dropping after the charge and discharge cycle is solved, and an efficient input maintenance rate is achieved.

CN119547238APending Publication Date: 2025-02-28GS YUASA INT LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380053145.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-12
Filing Date
2023-07-05
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The input power of existing power storage components decreases after the charge and discharge cycle, making it difficult to maintain efficient charging performance.

Method used

The positive electrode active material particles with an internal void ratio of less than 15% and graphite particles with an internal void ratio of less than 2% are used to form an electrode body, and at least a part of the electrode body is in a pressed state.

Benefits of technology

The input maintenance rate after the charge and discharge cycle is improved, ensuring the efficiency of the power storage components during repeated charge and discharge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

A power storage element according to one side of the present invention is provided with an electrode body in which a positive electrode having a positive electrode active material layer and a negative electrode having a negative electrode active material layer are overlapped with each other via a separator, the positive electrode active material layer containing positive electrode active material particles, and the internal porosity of the positive electrode active material particles being 15% or less. The negative electrode active material layer contains graphite particles, and the internal porosity of the graphite particles is 2% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electric storage element. Background Art

[0002] Non-aqueous electrolyte secondary batteries, represented by lithium-ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. As storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium-ion capacitors and electric double layer capacitors have also become widely used.

[0003] As a storage element, it is generally provided with an electrode body in which a positive electrode containing a positive electrode active material and a negative electrode containing a negative electrode active material are overlapped via a separator. Such an electrode body is housed in a container together with an electrolyte to form a storage element. As a negative electrode active material, carbon materials headed by graphite are widely used (see Patent Documents 1 and 2).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2005-222933

[0007] Patent Document 2: Japanese Patent Application Publication No. 2017-069039 Summary of the invention

[0008] In a storage element, it is ideal that the input is not easily reduced even if it is repeatedly charged and discharged. It should be noted that input refers to the energy (power: W) that can be absorbed per unit time when the storage element is charged. In other words, input refers to the input power during charging, which is an indicator of performance that can be charged efficiently.

[0009] An object of the present invention is to provide a power storage element having a high input retention rate after charge and discharge cycles.

[0010] An aspect of the present invention relates to a storage element comprising an electrode body formed by overlapping a positive electrode having a positive electrode active material layer and a negative electrode having a negative electrode active material layer via an insulating member; the positive electrode active material layer contains positive electrode active material particles, the internal porosity of the positive electrode active material particles is less than 15%, and the negative electrode active material layer contains graphite particles, the internal porosity of the graphite particles is less than 2%.

[0011] According to one aspect of the present invention, it is possible to provide a power storage element having a high input retention rate after charge and discharge cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is a perspective view showing an embodiment of an electric storage element.

[0013] Figure 2 This is a schematic diagram showing one embodiment of a power storage device constituted by a collection of a plurality of power storage elements. DETAILED DESCRIPTION

[0014] It can be understood from the following description and examples that the contents disclosed in this specification include the following contents.

[0015] [1]: A power storage device comprising an electrode body in which a positive electrode having a positive electrode active material layer and a negative electrode having a negative electrode active material layer are stacked with a separator interposed therebetween.

[0016] The positive electrode active material layer contains positive electrode active material particles, and the internal porosity of the positive electrode active material particles is 15% or less.

[0017] The negative electrode active material layer contains graphite particles, and the internal porosity of the graphite particles is 2% or less.

[0018] [2]: The energy storage device according to [1] above, wherein the positive electrode active material particles are secondary particles.

[0019] [3]: The energy storage device according to [1] or [2] above, wherein the positive electrode active material particles include a lithium transition metal composite oxide having an α-NaFeO 2 type crystal structure.

[0020] [4]: The electric storage device according to any one of [1] to [3] above, wherein at least a portion of the electrode body is in a pressed state.

[0021] First, the outline of the electric storage device disclosed in this specification will be described.

[0022] An aspect of the present invention relates to a storage element comprising an electrode body formed by overlapping a positive electrode having a positive electrode active material layer and a negative electrode having a negative electrode active material layer via an isolation member, wherein the positive electrode active material layer contains positive electrode active material particles, and the internal porosity of the positive electrode active material particles is less than 15%, and the negative electrode active material layer contains graphite particles, and the internal porosity of the graphite particles is less than 2%.

[0023] The input maintenance rate of the storage element after the charge and discharge cycle is high. The reason has not yet been determined, but it is speculated to be the following. Usually, in a storage element containing graphite particles in the negative electrode active material layer, the graphite particles expand with charging and discharging, and the positive electrode active material layer is pressed by the expanded negative electrode active material layer via the separator. If the positive electrode active material layer is pressed, the positive electrode active material particles in the positive electrode active material layer will be broken, and the electrical contact between the positive electrode active material particles and the positive electrode active material particles will be reduced, so the input will be reduced. In particular, in the case of positive electrode active material particles with a large internal porosity, it is easy to break even if they are not pressed strongly. In addition, graphite particles with a large internal porosity expand particularly large with charging and discharging, so even when positive electrode active material particles with a small internal porosity are used, it is easy to cause the positive electrode active material particles to break. In contrast, in the storage element involved in one aspect of the present invention, since graphite particles with small internal porosity and small expansion accompanying charge and discharge, and positive electrode active material particles with small internal porosity and not easy to crack are used, it is speculated that even if charge and discharge are repeated, the cracking of the positive electrode active material particles is suppressed and the input maintenance rate is high.

[0024] The "internal porosity" in positive electrode active material particles and graphite particles is the area ratio (porosity) of the voids within the particles in the cross section of the particles observed in the SEM images obtained using a scanning electron microscope (SEM) relative to the area of ​​the entire particle, and can be determined using the following steps.

[0025] (1) Preparation of test samples

[0026] The positive electrode and negative electrode to be measured were fixed with a thermosetting resin, respectively, and the cross-sections of the positive electrode and negative electrode fixed with the resin were exposed by ion milling to prepare samples for measurement.

[0027] It should be noted that the positive electrode and negative electrode to be measured are prepared by the following steps. When the positive electrode and negative electrode can be prepared before assembling the storage element, they can be used directly. In the case of preparing from the assembled storage element, first, the storage element is discharged at a constant current of 0.1C to the discharge end voltage during normal use, and the discharged state is obtained. The storage element in the discharged state is disassembled, the negative electrode is taken out, and the components (electrolyte, etc.) attached to the positive electrode and the negative electrode are thoroughly cleaned with dimethyl carbonate, and then dried under reduced pressure at room temperature for 24 hours. The operation from disassembly of the storage element to preparation of the positive electrode and negative electrode to be measured is carried out in a dry air atmosphere with a dew point below -40°C. Here, normal use refers to the case where the storage element is used under the charge and discharge conditions recommended or specified for the storage element.

[0028] (2) Acquisition of SEM images

[0029] In order to obtain SEM images (cross-sectional SEM images), JSM-7001F (manufactured by JEOL Ltd.) was used as a scanning electron microscope. The SEM image is used as a device for observing secondary electron images. The acceleration voltage is set to 15 kV. The observation magnification is set to a magnification at which the number of positive electrode active material particles or graphite particles appearing in one field of view is more than 3 and less than 15. The obtained SEM image is saved as an image file. In addition, various conditions such as spot diameter, operating distance, irradiation current, brightness, focus, etc. are appropriately set to make the outline of the positive electrode active material particles or graphite particles clear.

[0030] (3) Shearing of the contours of positive electrode active material particles or graphite particles

[0031] The contour of the positive electrode active material particles or graphite particles was cut from the acquired SEM image using the image cutting function of the image editing software Adobe Photoshop Elements 11. The contour of the positive electrode active material particles or graphite particles was selected outside the contour using the quick selection tool, and the portion other than the positive electrode active material particles or graphite particles was edited to a black background, thereby cutting the contour. At this time, if the number of positive electrode active material particles or graphite particles whose contours can be cut is less than 3, the SEM image was re-acquired until the number of positive electrode active material particles or graphite particles whose contours can be cut reaches 3 or more.

[0032] (4) Binarization

[0033] For the image of the first positive electrode active material particle or graphite particle among the cut positive electrode active material particles or graphite particles, the image analysis software PopImaging 6.00 is used to set the concentration 20% lower than the maximum intensity as the threshold value and perform binarization processing. The area on the side with high concentration is calculated by binarization processing as "the area S1 of the pores in the particle".

[0034] Next, the same first positive electrode active material particle or graphite particle image as before is binarized with a concentration of 10% as a threshold value. The outer edge of the positive electrode active material particle or graphite particle is determined by binarization, and the area inside the outer edge is calculated as the "area S0 of the entire particle".

[0035] The internal porosity (area ratio of the voids in the particle to the entire particle area) R1 in the first positive electrode active material particle or graphite particle is calculated by calculating the ratio of S1 to S0 (S1 / S0) using the calculated S1 and S0.

[0036] The above-mentioned binarization process is also performed on the images of the positive electrode active material particles or graphite particles after the second one among the cut positive electrode active material particles or graphite particles, and the area S1 and the area S0 are calculated. Based on the calculated area S1 and the area S0, the internal porosity R2, R3, ... of each positive electrode active material particle or graphite particle is calculated.

[0037] (5) Determination of internal void ratio

[0038] In the positive electrode active material particles or graphite particles, the internal porosity is determined by calculating the average value of all the internal porosities R1, R2, R3, ... calculated by the binarization process.

[0039] It should be noted that, instead of the scanning electron microscope used for the above-mentioned "acquisition of SEM images", the image editing software used for the "cutting of the contours of positive electrode active material particles or graphite particles", and the image analysis software used for the "binarization processing", devices and software capable of performing equivalent measurements, image editing and image analysis may also be used.

[0040] “Graphite” refers to the average lattice spacing (d) of the (002) plane determined by X-ray diffraction before charge or discharge or in the discharged state. 002 ) is greater than 0.33nm and less than 0.34nm. Here, the "discharge state" of the carbon material refers to a discharge state in which lithium ions can be fully released from the carbon material as the negative electrode active material during charge and discharge. For example, in a half-cell with a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metal Li as a counter electrode, the open circuit voltage is greater than 0.7V.

[0041] "Separator" refers to a component that performs electrical isolation while ensuring the conductivity of charge transfer ions between the positive electrode active material layer and the negative electrode active material layer. The separator may also be a component that is integrated with the positive electrode or the negative electrode, such as a layer (e.g., an inorganic particle layer) disposed on the surface of the positive electrode active material layer or the negative electrode active material layer.

[0042] The positive electrode active material particles are preferably secondary particles. Generally speaking, when the positive electrode active material particles are secondary particles, they are prone to rupture due to pressing. Therefore, when one aspect of the present invention is applied to a storage element in which the positive electrode active material particles are secondary particles, the effect of increasing the input maintenance rate after the charge and discharge cycle is particularly significant.

[0043] The "secondary particles" are particles formed by agglomeration of a plurality of primary particles. The "primary particles" are particles in which no grain boundaries are observed in appearance when observed under SEM.

[0044] The above-mentioned positive electrode active material particles preferably contain a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure. In general, particles of a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure are prone to cracking due to pressure. Therefore, when one aspect of the present invention is applied to a storage element in which the positive electrode active material particles contain a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure, the effect of increasing the input maintenance rate after charge and discharge cycles is particularly significant.

[0045] Preferably, at least a portion of the electrode body is in a pressed state. When at least a portion of the electrode body is in a pressed state, there are advantages such as increased initial input, discharge capacity, etc. due to increased electrical contact between active material particles. On the other hand, when at least a portion of the electrode body is in a pressed state, the positive electrode active material particles are prone to rupture with repeated charge and discharge. Therefore, when one aspect of the present invention is applied to a storage element in which at least a portion of the electrode body is in a pressed state, the effect of increasing the input maintenance rate after the charge and discharge cycle is particularly significant.

[0046] The following describes in detail a storage element, a storage device, a method for manufacturing a storage element, and other embodiments of an embodiment of the present invention. It should be noted that the names of the components (components) used in each embodiment may be different from the names of the components (components) used in the background art.

[0047] <Electrical storage element>

[0048] The storage element of one embodiment of the present invention comprises: an electrode body having a positive electrode, a negative electrode and a separator, an electrolyte, and a container for accommodating the electrode body and the electrolyte. The electrode body is formed by overlapping a positive electrode having a positive electrode active material layer and a negative electrode having a negative electrode active material layer via a separator. The electrode body is usually a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are stacked via a separator, or a wound type in which a positive electrode and a negative electrode are wound in a state in which they are stacked via a separator. The electrolyte exists in a state contained in the positive electrode, the negative electrode and the separator. The electrolyte can also be a non-aqueous electrolyte. As an example of a storage element, a secondary battery is described.

[0049] (positive electrode)

[0050] The positive electrode includes a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.

[0051] The positive electrode substrate has electrical conductivity. Whether it has "electrical conductivity" is determined by the volume resistivity 10 measured in accordance with JIS-H-0505 (1975). -2Ω·cm is the threshold value for judgment. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, or their alloys can be used. Among them, from the viewpoints of potential resistance, high conductivity and cost, aluminum or aluminum alloys are preferred. As the positive electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the viewpoint of cost, foil is preferred. Therefore, aluminum foil or aluminum alloy foil is preferred as the positive electrode substrate. As aluminum or aluminum alloy, A1085, A3003, A1N30, etc. specified in JIS-H-4000 (2014) or JIS-H4160 (2006) can be cited.

[0052] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate to the above range, the strength of the positive electrode substrate can be improved, and the energy density per unit volume of the storage element can be improved.

[0053] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer reduces the contact resistance between the positive electrode substrate and the positive electrode active material layer by containing a conductive agent such as carbon particles. The structure of the intermediate layer is not particularly limited, and for example, it contains a binder and a conductive agent.

[0054] The positive electrode active material layer contains positive electrode active material particles and optionally contains a conductive agent, a binder, a thickener, a filler, and other optional components.

[0055] The upper limit of the internal porosity of the positive electrode active material particles contained in the positive electrode active material layer is 15%, preferably 14%, more preferably 13%, further preferably 12%, further preferably 11%, and particularly preferably 10%. By making the internal porosity of the positive electrode active material particles below the above upper limit, the rupture of the positive electrode active material particles caused by pressing becomes less likely to occur, and the input maintenance rate after the charge and discharge cycle can be improved. The lower limit of the internal porosity of the positive electrode active material particles can be 0%, or it can be 0.1%, 1%, 3% or 5% (for example, 8%). The internal porosity of the positive electrode active material particles can be above any of the above lower limits and below any of the above upper limits. It should be noted that, without distinguishing the type of positive electrode active material, the internal porosity of the positive electrode active material particles is a value measured by taking any positive electrode active material particles extracted from all the positive electrode active material particles contained in the positive electrode active material layer according to the above steps as the object.

[0056] Positive electrode active material particles having an internal porosity of 15% or less can be produced by a known method.

[0057] The material constituting the positive electrode active material particles (positive electrode active material) can be appropriately selected from known positive electrode active materials. As positive electrode active materials for lithium ion secondary batteries, materials that can absorb and release lithium ions are generally used. Examples of positive electrode active materials include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel crystal structure, polyanion compounds, chalcogen compounds, sulfur, and the like. Examples of lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni (1-x) ]O2(0≤x<0.5), Li[Li x Ni γ CO (1-x-γ) ]O2 (0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x CO (1-x) ]O2(0≤x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2 (0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Ni γ Mn β CO (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), Li[Li x Ni γ CO β Al (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β) etc. As lithium transition metal composite oxides having a spinel crystal structure, Li x Mn2O4、Li x Ni γ Mn (2-γ) O4, etc. As polyanion compounds, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. can be mentioned. As chalcogenides, titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. can be mentioned. The atoms or polyanions in these materials can be partially replaced by atoms or anionic substances composed of other elements. The surfaces of these materials can also be coated with other materials. In the positive electrode active material layer, one of these materials can be used alone, or two or more can be mixed and used.

[0058] The positive electrode active material particles preferably include a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure. The lithium transition metal composite oxide preferably contains nickel, cobalt, manganese or aluminum, and more preferably contains nickel, cobalt and manganese. The content of nickel contained in the lithium transition metal composite oxide relative to all metal elements other than lithium is preferably 10 mol% to 80 mol%, and more preferably 20 mol% to 60 mol%. The content of cobalt contained in the lithium transition metal composite oxide relative to all metal elements other than lithium is preferably 10 mol% to 60 mol%, and more preferably 20 mol% to 50 mol%. The content of manganese contained in the lithium transition metal composite oxide relative to all metal elements other than lithium is preferably 5 mol% to 60 mol%, and more preferably 10 mol% to 50 mol%. By using such a lithium-transition metal composite oxide, energy density, etc. can be improved. In addition, when one embodiment of the present invention is applied to a storage element in which the positive electrode active material particles are such lithium transition metal composite oxides, the effect of increasing the input maintenance rate after charge and discharge cycles is particularly significant.

[0059] It should be noted that the composition ratio of the lithium transition metal composite oxide is the composition ratio before charging and discharging or when it reaches a fully discharged state by the following method. First, the storage element is discharged at a constant current of 0.05C to the lower limit voltage during normal use. The storage element in this state is disassembled, the positive electrode is taken out, and a half-cell is assembled with metal Li as the counter electrode. The positive electrode is adjusted to a fully discharged state by disassembling the positive electrode at a discharge current of 10 mA per 1 gram of positive electrode active material and discharging at a constant current until the positive electrode potential is 3.0 V vs. Li / Li+. The positive electrode is disassembled and taken out again. The components (electrolyte, etc.) attached to the taken out positive electrode are thoroughly washed with dimethyl carbonate, and the lithium transition metal composite oxide is collected after being dried under reduced pressure at room temperature for 24 hours. The collected lithium transition metal composite oxide is provided for measurement. The operation from disassembly of the storage element to collection of the lithium transition metal composite oxide for measurement is performed in a dry atmosphere with a dew point below -40°C.

[0060] The material of the positive electrode active material can be used alone or in combination of two or more. That is, the positive electrode active material particles can also be particles formed by mixing multiple positive electrode active material particles. In addition, each positive electrode active material particle can also be composed of multiple positive electrode active materials. The positive electrode active material preferably contains a lithium transition metal composite oxide in a ratio of 50% by mass or more (preferably 70% by mass to 100% by mass, more preferably 80% by mass to 100% by mass), and is more preferably composed of only lithium transition metal composite oxide.

[0061] The positive electrode active material particles may also be primary particles, but are preferably secondary particles. In the case where the positive electrode active material particles are secondary particles, there is a tendency for the surface area (reaction area) per unit mass to become larger and the DC resistance per unit mass to decrease. On the other hand, in general, in the case where the positive electrode active material particles are secondary particles, rupture caused by pressing is easy to occur. Therefore, in the case where one embodiment of the present invention is applied to a storage element in which the positive electrode active material particles are secondary particles, the effect of increasing the input maintenance rate after the charge and discharge cycle is particularly significant.

[0062] The average particle size of the positive electrode active material particles is, for example, preferably 0.1 μm to 20 μm, and more preferably 1 μm to 5 μm (for example, 3 μm to 5 μm). By making the average particle size of the positive electrode active material particles above the above lower limit, it is easy to manufacture or handle the positive electrode active material particles. By making the average particle size of the positive electrode active material particles below the above upper limit, the electrical conductivity of the positive electrode active material layer is improved. In addition, since cracks are more difficult to occur, the input maintenance rate after the charge and discharge cycle is further improved. "Average particle size" refers to the particle size distribution measured by the laser diffraction / scattering method based on the diluted solution after the particles are diluted in a solvent in accordance with JIS-Z-8825 (2013), and the volume standard cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50%.

[0063] In order to obtain positive electrode active material particles with a predetermined particle size, a pulverizer, a classifier, etc. can be used. As a pulverization method, for example, methods such as using a mortar, a ball mill, a sand mill, a vibrating ball mill, a planetary ball mill, a jet mill, a reverse jet mill, a rotating airflow jet mill or a sieve can be cited. Wet pulverization coexisting with organic solvents such as water or hexane can also be used in the pulverization process. As a classification method, a sieve, a wind classifier, etc. can be used, and dry or wet methods can be used as needed.

[0064] The BET specific surface area of ​​the positive electrode active material particles can be, for example, 1.2 m 2 / g~15m 2 / g (e.g. 1.2m 2 / g~1.8m 2 The BET specific surface area of ​​the positive electrode active material particles is preferably 1.5 m 2 / g~10m 2 / g, more preferably 1.5m 2 / g~5.0m 2 In some embodiments, the BET specific surface area of ​​the positive electrode active material particles may be 2.0 m 2 / g~5.0m 2When the BET specific surface area of ​​the positive electrode active material particles is within the above range, the input retention rate after charge and discharge cycles can be improved and other charge and discharge performances can also be sufficiently excellent.

[0065] The "BET specific surface area" of the positive electrode active material particles is a value obtained from the adsorption isotherm using the nitrogen adsorption method for the positive electrode active material particles before charge and discharge or when they are in a fully discharged state by the following method. First, the storage element is discharged at a constant current of 0.05C to the lower limit voltage during normal use. The storage element in this state is disassembled, the positive electrode is removed, and a half-cell is assembled with metal Li as the counter electrode. At a discharge current of 10 mA per gram of the positive electrode active material, a constant current discharge is performed until the positive electrode potential is 3.0 V vs. Li / Li + , adjust the positive electrode to a fully discharged state. Disassemble and remove the positive electrode again. Use dimethyl carbonate to thoroughly clean the components (electrolyte, etc.) attached to the removed positive electrode, dry under reduced pressure at room temperature for 24 hours, and then collect the positive electrode active material particles. The collected positive electrode active material particles are provided for measurement. The operation from disassembly of the storage element to collection of the positive electrode active material particles for measurement is carried out in a dry air atmosphere with a dew point below -40°C.

[0066] The BET specific surface area is determined according to the following steps. 1.00 g of the positive electrode active material particles are added to the sample tube for measurement and dried under reduced pressure at 120°C for 12 hours. Next, the adsorption isotherm is measured in the range of relative pressure P / P0 (P0 = about 770 mmHg) from 0 to 1 by the nitrogen adsorption method using liquid nitrogen. Five points are extracted from the region of P / P0 = 0.05 to 0.3 of the obtained adsorption isotherm, and BET is plotted, and the BET specific surface area is calculated based on the y-intercept and slope of the straight line.

[0067] The content of the positive electrode active material particles in the positive electrode active material layer is preferably 50% to 99% by mass, more preferably 70% to 98% by mass, and further preferably 80% to 95% by mass. By setting the content of the positive electrode active material particles in the above range, both high energy density and manufacturability of the positive electrode active material layer can be achieved.

[0068] The conductive agent is not particularly limited as long as it is a material with conductivity. As such a conductive agent, for example, carbon materials, metals, conductive ceramics, etc. can be mentioned. As carbon materials, graphite, non-graphite carbon, graphene-based carbon, etc. can be mentioned. As non-graphite carbon, carbon nanofibers, pitch-based carbon fibers, carbon black, etc. can be mentioned. As carbon black, furnace black, acetylene black, Ketjen black, etc. can be mentioned. As graphene-based carbon, graphene, carbon nanotubes (CNT), fullerene, etc. can be mentioned. As the shape of the conductive agent, powder, fiber, etc. can be mentioned. As the conductive agent, one of these materials can be used alone, or two or more can be mixed and used. In addition, these materials can also be used in combination. For example, a material obtained by combining carbon black and CNT can also be used. Among these, from the viewpoint of electrical conductivity and coating properties, carbon black is preferred, and acetylene black is preferred.

[0069] The content of the conductive agent in the positive electrode active material layer is preferably 1% to 10% by mass, and more preferably 3% to 9% by mass. When the content of the conductive agent is within the above range, the energy density of the electric storage device can be increased.

[0070] As adhesives, for example, there can be mentioned thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic acid, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0071] The content of the binder in the positive electrode active material layer is preferably 1% to 10% by mass, and more preferably 2% to 9% by mass. When the content of the binder is within the above range, the positive electrode active material particles can be stably retained.

[0072] As the thickener, for example, polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose can be cited. When the thickener has a functional group that reacts with lithium or the like, the functional group can be deactivated in advance by methylation or the like. When the positive electrode active material layer contains a thickener, the content of the thickener in the positive electrode active material layer is, for example, 0.1 mass % to 10 mass %. The content of the thickener in the positive electrode active material layer can be 5 mass % or less, or 1 mass % or less, or 0 mass %.

[0073] The filler is not particularly limited. As fillers, polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, aluminum hydroxide, carbonates such as calcium carbonate, insoluble ionic crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, mica and other mineral resources or their artificial products can be cited. In the case where the positive electrode active material layer contains fillers, the content of the filler in the positive electrode active material layer is, for example, 0.1% to 10% by mass. The content of the filler in the positive electrode active material layer can be 5% by mass or less, or 1% by mass or less, or 0% by mass.

[0074] The positive electrode active material layer may also contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than positive electrode active material particles, conductive agents, adhesives, thickeners, and fillers.

[0075] The porosity of the positive electrode active material layer is preferably 30% to 50%, and more preferably 35% to 47% (e.g., 40% to 47%). By making the porosity of the positive electrode active material layer within the above range, the input maintenance rate after the charge and discharge cycle can be further improved. The porosity of the positive electrode active material layer can be adjusted by the average particle size of the positive electrode active material particles, the presence or absence of pressure when making the positive electrode, the strength, etc.

[0076] The porosity of the active material layer (positive electrode active material layer and negative electrode active material layer) refers to the true density of the active material layer calculated based on the true density of each component constituting the active material layer, and the apparent density of the active material layer, which is a value obtained by the following formula (1). The apparent density of the active material layer refers to the value obtained by dividing the mass of the active material layer by the apparent volume of the active material layer. The apparent volume refers to the volume including the void portion, which can be obtained as the product of the average thickness and area of ​​the active material layer. The average thickness of the active material layer is the average value of the thickness measured at any 5 positions.

[0077] Porosity (%) = 100 - (apparent density / true density) × 100... (1)

[0078] The mass per unit area of ​​the positive electrode active material layer is not particularly limited, but is preferably 1 mg / cm 2 ~10mg / cm 2, more preferably 4 mg / cm 2 ~8mg / cm 2 (e.g. 5mg / cm 2 ~7.5mg / cm 2 ). In a storage element having a positive electrode active material layer whose mass per unit area is within the above range, the application effect of the present configuration can be better exerted. It should be noted that the "mass per unit area of ​​the positive electrode active material layer" refers to the mass per unit area of ​​one positive electrode active material layer. For example, in a case where the positive electrode has a positive electrode substrate and positive electrode active material layers are provided on both sides of the positive electrode substrate, the "mass per unit area of ​​the positive electrode active material layer" is the mass per unit area of ​​the positive electrode active material layer on one side.

[0079] The preparation of the positive electrode can be carried out, for example, by coating the positive electrode mixture slurry directly or via an intermediate layer on the positive electrode substrate and drying it. After drying, it can also be pressed as needed. The positive electrode mixture slurry contains positive electrode active material particles and various components constituting the positive electrode active material layer such as a conductive agent and a binder as arbitrary components. The positive electrode mixture slurry usually further contains a dispersion medium.

[0080] (negative electrode)

[0081] The negative electrode comprises a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The structure of the intermediate layer is not particularly limited and can be selected from the structures exemplified in the above-mentioned positive electrode.

[0082] The negative electrode substrate has conductivity. As the material of the negative electrode substrate, metals such as copper, nickel, stainless steel, nickel-plated steel, or their alloys, carbon materials, etc. can be used. Among them, copper or copper alloys are preferred. As the negative electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the perspective of cost, foil is preferred. Therefore, as the negative electrode substrate, copper foil or copper alloy foil is preferred. As examples of copper foil, rolled copper foil, electrolytic copper foil, etc. can be cited.

[0083] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By making the average thickness of the negative electrode substrate within the above range, the strength of the negative electrode substrate can be improved, and the energy density per unit volume of the storage element can be improved.

[0084] The negative electrode active material layer contains graphite particles. The negative electrode active material layer contains other negative electrode active materials other than graphite particles, conductive agents, binders, thickeners, fillers and other arbitrary components as needed. Conductive agents, binders, thickeners, fillers and other arbitrary components can be selected from the materials exemplified in the above-mentioned positive electrode.

[0085] The negative electrode active material layer may also contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than graphite particles and negative electrode active materials, conductive agents, binders, thickeners, and fillers.

[0086] Graphite particles are components that act as negative electrode active materials. The upper limit of the internal porosity of the graphite particles contained in the negative electrode active material layer is 2%, preferably 1%, more preferably 0.5%, and further preferably 0.1%. By making the internal porosity of the graphite particles below the above upper limit, the expansion of the graphite particles during charge and discharge is suppressed, and the pressure on the positive electrode active material layer caused by the expanded negative electrode active material layer is suppressed, so the rupture of the positive electrode active material particles is suppressed, and as a result, the input maintenance rate after the charge and discharge cycle can be improved. The lower limit of the internal porosity of the graphite particles can be 0% or 0.01%. The internal porosity of the graphite particles can be above any of the above lower limits and below any of the above upper limits. It should be noted that, without distinguishing the types of graphite particles, the internal porosity of the graphite particles is a value measured for any graphite particles extracted from all the graphite particles contained in the negative electrode active material layer according to the above steps.

[0087] Graphite particles having an internal porosity of 2% or less can be obtained by, for example, compressing conventional graphite.

[0088] The graphite particles may be natural graphite or artificial graphite, preferably natural graphite. By using natural graphite as the graphite particles, the initial resistance of the storage element can be reduced, and the input retention rate after charge and discharge cycles can be further improved.

[0089] Natural graphite is a general term for graphite extracted from natural resources. Graphite particles composed of natural graphite can also be spheroidized natural graphite particles obtained by spheroidizing flaky natural graphite and the like. Natural graphite can also be a substance in which four peaks appear in the range of a diffraction angle 2θ of 40° to 50° in an X-ray diffraction pattern using CuKα rays measured before charge and discharge or in a discharged state. These four peaks are considered to be two peaks from a hexagonal crystal structure and two peaks from a rhombohedral crystal structure. In the case of artificial graphite, it is generally believed that only two peaks from a hexagonal crystal structure appear. In the X-ray diffraction pattern, the ratio of the peak intensity from the (012) plane to the peak intensity from the (100) plane ((012) / (100)) is preferably 0.3 or more, and more preferably 0.4 or more. The above peak intensity ratio ((012) / (100)) is preferably 0.6 or less. Here, the (100) plane comes from the hexagonal crystal structure, and the (012) plane comes from the rhombohedral crystal structure.

[0090] The average particle size of the graphite particles is preferably 1 μm to 25 μm, more preferably 4 μm to 20 μm, and further preferably 5 μm to 15 μm (for example, 6 μm or more and less than 10 μm). By making the average particle size of the graphite particles within the above range, the input maintenance rate after the charge and discharge cycle can be further improved. In order to obtain graphite particles with a specified particle size, a pulverizer, a classifier, etc. can be used. The pulverization method and the classification method can be selected from the methods exemplified by the above-mentioned positive electrode active material particles.

[0091] The content of graphite particles in the negative electrode active material layer is preferably 60 mass % to 99 mass %, more preferably 90 mass % to 98 mass %, and sometimes more preferably 95 mass %, 97 mass % or more, or 98 mass % or more. By making the content of graphite particles within the above range, it is possible to take into account the high energy density and manufacturability of the negative electrode active material layer, and it is possible to further improve the input maintenance rate after the charge and discharge cycle.

[0092] The negative electrode active material layer may also include other negative electrode active materials other than graphite particles. As other negative electrode active materials, various negative electrode active materials known in the past can be used. Among them, the content of graphite particles contained in the negative electrode active material layer is preferably 90% by mass or more, more preferably 99% by mass or more, and may be substantially 100% by mass. In the case of applying one embodiment of the present invention to a storage element mainly using graphite particles as a negative electrode active material, the effect of increasing the input maintenance rate after charge and discharge cycles is particularly significant.

[0093] When the negative electrode active material layer contains a conductive agent, the content of the conductive agent in the negative electrode active material layer is, for example, 1% to 10% by mass. The content of the conductive agent in the negative electrode active material layer is preferably 5% by mass or less, and sometimes more preferably 2% by mass or less, 1% by mass or less, 0.1% by mass or less, or 0% by mass. When the content of the conductive agent in the negative electrode active material layer is small or does not contain a conductive agent, the content of negative electrode active materials such as graphite particles can be increased, and the energy density can be improved. It should be noted that, without distinguishing the type of graphite particles, the graphite particles in the negative electrode active material layer are not equivalent to the conductive agent in the negative electrode active material layer.

[0094] The content of the binder in the negative electrode active material layer is preferably 0.1% by mass to 10% by mass, and more preferably 1% by mass to 5% by mass. When the content of the binder is within the above range, graphite particles and the like can be stably retained.

[0095] When the negative electrode active material layer contains a thickener, the content of the thickener in the negative electrode active material layer is preferably 0.1% by mass to 5% by mass.

[0096] When the negative electrode active material layer contains fillers, the content of the fillers in the negative electrode active material layer is, for example, 0.1 mass % to 10 mass %. The content of the fillers in the negative electrode active material layer may be 5 mass % or less, 1 mass % or less, or 0 mass %. When the content of the fillers in the negative electrode active material layer is small or does not contain fillers, the content of negative electrode active materials such as graphite particles can be increased, and the energy density can be improved.

[0097] The porosity of the negative electrode active material layer is preferably 35% to 50%, and more preferably 37% to 45%. By making the porosity of the negative electrode active material layer below the above upper limit, the energy density is improved. On the other hand, generally, the lower the porosity of the negative electrode active material layer, the easier it is for the negative electrode active material layer to expand with charge and discharge. In contrast, in an electric storage element according to one embodiment of the present invention, by using graphite particles having an internal porosity of less than 2%, even when the porosity of the negative electrode active material layer is low, the expansion of the negative electrode active material layer with charge and discharge becomes smaller, and the input maintenance rate after the charge and discharge cycle can be improved.

[0098] The mass per unit area of ​​the negative electrode active material layer is not particularly limited, but is preferably 1 mg / cm 2 ~10mg / cm 2 , more preferably 2 mg / cm 2 ~5mg / cm 2. In a storage element having a negative electrode active material layer whose mass per unit area is within the above range, the application effect of the present configuration can be better exerted. It should be noted that the "mass per unit area of ​​the negative electrode active material layer" refers to the mass per unit area of ​​one negative electrode active material layer. For example, in a case where the negative electrode has a negative electrode substrate and negative electrode active material layers are respectively provided on both sides of the negative electrode substrate, the "mass per unit area of ​​the negative electrode active material layer" is the mass per unit area of ​​the negative electrode active material layer on one side.

[0099] The production of the negative electrode can be carried out, for example, by coating the negative electrode mixture slurry directly or via an intermediate layer on the negative electrode substrate and drying it. After drying, it can also be pressed as needed. It should be noted that in the negative electrode, since graphite particles with an internal porosity of less than 2% are used, a negative electrode active material layer with a sufficiently high density can be formed even without pressurization or with a weak pressurization intensity. The negative electrode mixture slurry contains graphite particles and various components constituting the negative electrode active material layer such as a conductive agent and a binder as arbitrary components. The negative electrode mixture slurry usually further contains a dispersion medium.

[0100] (Isolator)

[0101] The separator can be appropriately selected from known separators. As the separator, for example, a separator consisting only of a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and an adhesive is formed on one or both surfaces of the substrate layer, etc. can be used. As the shape of the substrate layer of the separator, woven fabrics, non-woven fabrics, and porous resin films can be cited. Among these shapes, porous resin films are preferred from the viewpoint of strength, and non-woven fabrics are preferred from the viewpoint of electrolyte retention. As the material of the substrate layer of the separator, from the viewpoint of insulation function, for example, polyolefins such as polyethylene and polypropylene are preferred, and from the viewpoint of resistance to oxidative decomposition, polyimides, aromatic polyamides, etc. are preferred. As the substrate layer of the separator, a material composited with these resins can also be used.

[0102] The heat-resistant particles contained in the heat-resistant layer preferably have a mass reduction of 5% or less when the temperature is increased from room temperature to 500°C in an air atmosphere at 1 atmosphere pressure, and more preferably have a mass reduction of 5% or less when the temperature is increased from room temperature to 800°C. As materials whose mass reduction is less than a specified value, inorganic compounds can be cited. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; and sparingly soluble ionic crystals such as calcium fluoride, barium fluoride, and barium titanate. Covalent crystals such as silicon and diamond. Substances derived from mineral resources such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or their artificial products. As inorganic compounds, monomers or composites of these substances can be used alone, or two or more can be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of safety of the electric storage device.

[0103] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and preferably 20% by volume or more from the viewpoint of discharge performance. Here, the "porosity" refers to a value based on volume, and is a value measured using a mercury porosimeter.

[0104] As a separator, a polymer gel composed of a polymer and an electrolyte can be used. As the polymer, for example, polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyvinylidene fluoride, etc. can be cited. The use of polymer gel can have the effect of suppressing leakage. As a separator, a porous resin film or non-woven fabric as described above can be used together with the polymer gel.

[0105] As described above, the separator may also be a layer integrated with the positive electrode or the negative electrode. As such a layer, an inorganic particle layer stacked on the surface of the positive electrode active material layer or the negative electrode active material layer may be cited. The inorganic particle layer, for example, comprises inorganic particles and a binder. As such a separator layer, it is usually an insulating porous layer.

[0106] (Electrolytes)

[0107] The electrolyte may be appropriately selected from known electrolytes. The electrolyte may be a non-aqueous electrolyte or a non-aqueous electrolyte solution. The non-aqueous electrolyte solution includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent.

[0108] As non-aqueous solvent, it can be appropriately selected from known non-aqueous solvents. Non-aqueous solvents include cyclic carbonate, linear carbonate, carboxylate, phosphoric acid ester, sulfonic acid ester, ether, amide, nitrile, etc. As non-aqueous solvent, a solvent in which a part of hydrogen atoms contained in these compounds is replaced by halogen atoms can be used.

[0109] Examples of the cyclic carbonate include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), chloroethylene carbonate, fluorinated ethylene carbonate (FEC), difluorinated ethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, and 1,2-diphenylvinylene carbonate. Among them, EC is preferred.

[0110] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, etc. Among them, EMC is preferred.

[0111] As the non-aqueous solvent, preferably a cyclic carbonate or a chain carbonate is used, and more preferably a cyclic carbonate and a chain carbonate are used together. By using a cyclic carbonate, the dissociation of the electrolyte salt can be promoted and the ion conductivity of the non-aqueous electrolyte can be improved. By using a chain carbonate, the viscosity of the non-aqueous electrolyte can be controlled to decrease. When a cyclic carbonate and a chain carbonate are used together, the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate: chain carbonate) is, for example, preferably in the range of 5:95 to 50:50.

[0112] As the electrolyte salt, it is possible to appropriately select from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, Among them, lithium salts are preferred.

[0113] As lithium salts, inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, LiN(SO2F)2, lithium oxalate salts such as lithium di(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), difluorobis(oxalate)phosphate (LiFOP), lithium salts having halogenated hydrocarbon groups such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, LiC(SO2C2F5)3, etc. can be cited. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.

[0114] The content of the electrolyte salt in the non-aqueous electrolyte is preferably 0.1 mol / dm 3~2.5mol / dm 3 , more preferably 0.3 mol / dm 3 ~2.0mol / dm 3 , more preferably 0.5 mol / dm 3 ~1.7mol / dm 3 , particularly preferably 0.7 mol / dm 3 ~1.5mol / dm 3 By setting the content of the electrolyte salt to be within the above range, the ion conductivity of the non-aqueous electrolyte can be improved.

[0115] In addition to the non-aqueous solvent and the electrolyte salt, the non-aqueous electrolyte may also contain additives. Examples of the additives include aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydride of terphenyl, cyclohexylbenzene, tert-butylbenzene, tert-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, and cyclohexanedicarboxylic anhydride; vinyl sulfite, propylene sulfite, and disulfite; Methyl ester, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, vinyl sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathialane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathialane, thioanisole, diphenyl disulfide, dipyridine disulfide, 1,3-propylene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, etc. These additives may be used alone or in combination of two or more.

[0116] The content of the additive contained in the non-aqueous electrolyte is preferably 0.01% to 10% by mass, more preferably 0.1% to 7% by mass, further preferably 0.2% to 5% by mass, and particularly preferably 0.3% to 3% by mass relative to the mass of the entire non-aqueous electrolyte. By making the content of the additive within the above range, the capacity retention performance or cycle performance after high temperature storage can be improved, and the safety can be further improved.

[0117] As the electrolyte, a solid electrolyte may be used, or a non-aqueous electrolyte and a solid electrolyte may be used in combination.

[0118] The solid electrolyte can be selected from any material that has ion conductivity and is solid at room temperature (e.g., 15° C. to 25° C.), such as lithium, sodium, and calcium. Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and polymer solid electrolytes.

[0119] As sulfide solid electrolytes, in the case of lithium ion secondary batteries, for example, Li2S-P2S5, LiI-Li2S-P2S5, Li 10 Ge-P2S 12 wait.

[0120] (Pressing of the electrode body, etc.)

[0121] At least a portion of the electrode body may be in a pressed state in the container. Specifically, in the electrode body, at least a portion along the thickness direction (stacking direction) of each layer may be in a pressed state. It should be noted that a portion of the electrode body (for example, a pair of curved portions in a flat wound electrode body, etc.) may not be in a pressed state. In addition, a portion of the flat portion of a stacked electrode body and a flat wound electrode body, for example, may be in a state where only the central portion is pressed. In the case where at least a portion of the electrode body is in a pressed state, the initial input increases due to increased electrical contact between the active material particles, etc. In addition, in the case of applying an embodiment of the present invention to a storage element in which at least a portion of the electrode body is in a pressed state, the effect of increasing the input maintenance rate after the charge and discharge cycle is particularly significant.

[0122] The pressing of at least a portion of the electrode body (the application of a load) can be performed, for example, by using a pressurizing member that pressurizes the container from the outside. The pressurizing member can also be a constraining member that constrains the shape of the container. The pressurizing member (constraining member) is, for example, configured to clamp at least a portion of the electrode body from both sides in the thickness direction via the container for pressing. In the electrode body, the pressed surface is directly or via other components in contact with the inner surface of the container. Therefore, at least a portion of the electrode body is pressed by the pressurized container. As a pressurizing member (constraining member), for example, a restraining belt, a metal frame, etc. can be cited. For example, in a metal frame, it can be configured so that the load can be adjusted using bolts, etc. In addition, a plurality of storage elements can be arranged side by side along the thickness direction of the electrode body, and a frame can be used to fix the plurality of storage elements in a state where they are pressurized from both ends in the thickness direction. In addition, it is also possible to be in a state where at least a portion of the electrode body is pressed by a method such as reducing the pressure inside the container without using a pressurizing member.

[0123] The pressure applied to the electrode body in which at least a portion of the electrode body is pressed is preferably 0.01 MPa to 5 MPa, and more preferably 0.1 MPa to 1 MPa. Here, the pressure applied to the electrode body is a value measured by the following method.

[0124] First, the storage element is discharged with a constant current to the lower limit voltage during normal use, and then placed on an X-ray computed tomography (CT) device. Scan in a direction parallel to the thickness direction of the electrode body to confirm whether the electrode body is in direct or indirect contact with the inner surface of the container. When the electrode body is not in direct or indirect contact with the inner surface of the container, the pressure applied to the electrode body is set to 0MPa (the electrode body is not in a pressed state). When the electrode body is in direct or indirect contact with the inner surface of the container, an X-ray transmission image of the electrode body is taken to measure the maximum thickness in the stacking direction of the electrode body. The storage element is disassembled and the electrode body is taken out, and placed on an Autograph testing machine. A load is gradually applied to the electrode body by the Autograph testing machine, and the electrode body is compressed to the maximum thickness in the thickness direction of the electrode body measured by the X-ray transmission image. The load measured by the Autograph testing machine at this time is used as the load applied to the electrode body. The value obtained by dividing the load applied to the electrode body by the area of ​​the contact surface between the Autograph testing machine and the electrode body is used as the pressure applied to the electrode body. In addition, although a load is usually applied to a pair of opposing surfaces of the electrode body using a container, the area of ​​only one of the pair of surfaces is used as the area of ​​the surface to which the load is applied.

[0125] The storage element according to one embodiment of the present invention may also be constrained by a pressure member or the like to have a certain thickness (certain size) in a container. In this case, at least a portion of the electrode body may be in a pressed state or may not be in a pressed state. For example, at the stage just after the storage element is manufactured, even if the electrode body is not in a pressed state, as the electrode body expands during the charge and discharge cycle, as a result, the container constrained by the pressure member or the like may cause at least a portion of the electrode body to be in a pressed state.

[0126] The shape of the electric storage element of the present embodiment is not particularly limited, and examples thereof include cylindrical batteries, square batteries, flat batteries, coin batteries, and button batteries.

[0127] Figure 1 The electric storage element 1 is shown as an example of a square battery. It should be noted that this figure is also a view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a square container 3. The positive electrode is electrically connected to a positive terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative terminal 5 via a negative electrode lead 51.

[0128] <Electricity storage device>

[0129] The storage element of this embodiment can be installed as a storage unit (battery module) composed of a plurality of storage elements in an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), etc., a car power source, a personal computer, a communication terminal, etc. In this case, the technology of the present invention can be applied to at least one storage element contained in the storage unit.

[0130] Figure 2 , an example of an electric storage device 30 is shown in which an electric storage unit 20 formed by aggregating two or more electrically connected electric storage elements 1 is further assembled. The electric storage device 30 may also include a bus bar (not shown) electrically connecting the two or more electric storage elements 1, a bus bar (not shown) electrically connecting the two or more electric storage units 20, etc. The electric storage unit 20 or the electric storage device 30 may also include a state monitoring device (not shown) for monitoring the state of the one or more electric storage elements.

[0131] <Method for manufacturing energy storage device>

[0132] The manufacturing method of the storage element of this embodiment can be appropriately selected from known methods. The manufacturing method, for example, comprises the following steps: preparing an electrode body, preparing an electrolyte, and storing the electrode body and the electrolyte in a container. Preparing the electrode body includes: preparing a positive electrode and a negative electrode, and forming the electrode body by stacking or winding the positive electrode and the negative electrode through a separator.

[0133] The method of storing the electrolyte in the container can be appropriately selected from known methods. For example, when a non-aqueous electrolyte is used as the electrolyte, the non-aqueous electrolyte is injected from an injection port formed on the container, and then the injection port is sealed. The manufacturing method may further include: pressurizing from the outside of the container storing the electrode body or depressurizing the inside of the container storing the electrode body, so that at least a portion of the electrode body is in a pressed state.

[0134] <Other embodiments>

[0135] It should be noted that the storage element of the present invention is not limited to the above-mentioned embodiment, and various changes can be made within the scope of the gist of the present invention. For example, the structure of another embodiment can be added to the structure of one embodiment, and a part of the structure of one embodiment can be replaced with the structure of another embodiment or a known technology. Furthermore, a part of the structure of one embodiment can be deleted. In addition, a known technology can be added to the structure of one embodiment.

[0136] In the above embodiment, the case where the storage element is used for a rechargeable non-aqueous electrolyte secondary battery (e.g., a lithium ion secondary battery) is described, but the type, shape, size, capacitance, etc. of the storage element are arbitrary. The present invention can also be applied to capacitors such as various secondary batteries, double-layer capacitors or lithium ion capacitors. The present invention can also be applied to storage elements using aqueous electrolytes as electrolytes.

[0137] Example

[0138] The present invention is further described in detail below by way of examples. The present invention is not limited to the following examples.

[0139] [Example 1]

[0140] (Production of positive electrode)

[0141] As positive electrode active material particles, particles having an internal porosity of 10%, an average particle size of 4 μm, and a BET specific surface area of ​​1.5 m 2 / g secondary particles, namely LiNi 1 / 3 CO 1 / 3 Mn 1 / 3 O2 (positive electrode active material particles A1).

[0142] The positive electrode mixture slurry is prepared using the above-mentioned positive electrode active material particles A1, acetylene black (AB) as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersion medium. It should be noted that the mass ratio of the positive electrode active material particles A1, AB and PVDF is 93:4.5:2.5 (converted in terms of solid content). The positive electrode mixture slurry is applied to both sides of the aluminum foil serving as the positive electrode substrate and dried. Then, roller pressing is performed to obtain a positive electrode. The porosity of the positive electrode active material layer in the obtained positive electrode is 45%, and the mass per unit area of ​​the positive electrode active material layer is 7 mg / cm 2 .

[0143] (Production of negative electrode)

[0144] As graphite particles, graphite particles A having an internal porosity of 0.03% and an average particle size of 8 μm were prepared. The graphite particles A were prepared by compressing natural graphite.

[0145] A negative electrode mixture slurry is prepared using the above-mentioned graphite particles A, styrene-butadiene rubber (SBR) as a binder, carboxymethyl cellulose (CMC) as a thickener, and water as a dispersion medium. It should be noted that the mass ratio of graphite particles A, SBR, and CMC is 98:1:1 (converted in terms of solid content). The negative electrode mixture slurry is applied to both sides of a copper foil serving as a negative electrode substrate and dried. Rolling is then performed to obtain a negative electrode. The porosity of the negative electrode active material layer in the obtained negative electrode is 40%, and the mass per unit area of ​​the negative electrode active material layer is 4 mg / cm 2 .

[0146] (Electrolytes)

[0147] In a solvent of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate mixed in a volume ratio of 30:35:35, 1.2 mol / dm 3 The concentration of LiPF6 is dissolved to obtain an electrolyte.

[0148] (Isolator)

[0149] A polyolefin microporous film was used as the separator.

[0150] (Assembly of energy storage elements)

[0151] The positive electrode, negative electrode and separator are used to obtain a flat wound electrode body. The electrode body is placed in a square container, an electrolyte is injected and the container is sealed to obtain the storage element of Example 1. It should be noted that the storage element is constrained in the thickness direction of the storage element container by a constraining member, and the flat portion of the electrode body is in a pressed state.

[0152] [Example 2 and Comparative Examples 1 to 4]

[0153] Except having used the positive electrode active material particles and graphite particles described in Table 1, the same procedure as in Example 1 was carried out to obtain electric storage devices of Example 2 and Comparative Examples 1 to 4.

[0154] In addition, the physical properties of each positive electrode active material particle and each graphite particle in Table 1 are as follows.

[0155] Positive electrode active material particles A1: internal porosity 10%, average particle size 4 μm, BET specific surface area 1.5 m 2 / g,LiNi 1 / 3 CO 1 / 3 Mn 1 / 3 O2 (secondary particles)

[0156] Positive electrode active material particles A2: internal porosity 10%, average particle size 4 μm, BET specific surface area 1.5 m 2 / g,LiNi 0.50 CO0.35 Mn 0.15 O2 (secondary particles)

[0157] Positive electrode active material particles B1: internal porosity 19%, average particle size 4 μm, BET specific surface area 2 m 2 / g,LiNi 1 / 3CO 1 / 3 Mn 1 / 3 O2 (secondary particles)

[0158] Graphite particles A: internal porosity 0.03%, average particle size 8 μm

[0159] Graphite particles B: internal porosity 3%, average particle size 10 μm

[0160] [evaluate]

[0161] (1) Initial charge and discharge

[0162] Each of the obtained storage elements was initially charged and discharged under the following conditions. In a thermostatic chamber at 25°C, constant current charging was performed with a charging current of 1.0C and a charge end voltage of 4.1V, and then constant voltage charging was performed at 4.1V. The charging end condition was set until the total charging time reached 3 hours. Then, a rest period of 10 minutes was set. Constant current discharge was performed with a discharge current of 1.0C and a discharge end voltage of 3.0V.

[0163] (2) Initial input

[0164] For each storage element after the initial charge and discharge, a constant current charge is performed at 1.0C at 25°C to a SOC of 55%. Next, charge at a current of 2C, 4C, 6C, 12C or 18C for 10 seconds. After each charge is completed, a constant current discharge is performed at a current of 0.5C to a SOC of 55%. The relationship between the current in each charge and the voltage in the first second after the start of charging is plotted, and the DC resistance is calculated based on the slope of the straight line obtained from the 5-point graph. Based on the calculated DC resistance, the input (input power; W) after 1 second after the start of charging is calculated using the formula {the difference between the voltage before charging and the upper limit voltage (4.3V)} / DC resistance × upper limit voltage (4.3V) as the initial input.

[0165] (3) Charge and discharge cycle test

[0166] Next, each storage element was discharged at a constant current of 1.0C at 25°C. After the SOC reached 0%, it was charged at a constant current of 0.5C to SOC50%. Next, it was stored in a constant temperature chamber at 55°C for 4 hours. Next, it was charged at a constant current of 8C to a voltage equivalent to SOC80%, and then it was discharged at a constant current of 8C to a voltage equivalent to SOC20%. There was no rest time after the above charging and discharging, and the above charging and discharging cycle was repeated for 250 hours.

[0167] (3) Input after charge and discharge cycle test

[0168] Then, the input after the charge-discharge cycle test was obtained by the same procedure as the procedure for obtaining the initial input. For each power storage element, the percentage of the input after the charge-discharge cycle test relative to the initial input was obtained as the input maintenance rate. The results are shown in Table 1.

[0169] [Table 1]

[0170]

[0171] As shown in Table 1, in each storage element of Examples 1 and 2 using positive electrode active material particles A1 and A2 having an internal porosity of less than 15%, and graphite particles A having an internal porosity of less than 2%, the input retention rate was greater than 95%, and a higher input retention rate after charge and discharge cycles was obtained compared with Comparative Examples 1 to 4.

[0172] It should be noted that, according to the comparison between Comparative Example 1 and Comparative Example 3, when the internal porosity of the graphite particles exceeds 2%, the effect of improving the input maintenance rate by using a substance with an internal porosity of 15% or less as the positive electrode active material particles cannot be confirmed. In addition, according to the comparison between Comparative Example 2 and Comparative Example 3, when the internal porosity of the positive electrode active material particles exceeds 15%, the effect of improving the input maintenance rate by using a substance with an internal porosity of 2% or less as the graphite particles cannot be confirmed. It was confirmed that the effect of increasing the input maintenance rate after the charge and discharge cycle began to be exerted by combining the positive electrode active material particles with an internal porosity of 15% or less and the graphite particles with an internal porosity of 2% or less.

[0173] Industrial Applicability

[0174] The present invention can be applied to a power storage element used as a power source for electronic devices such as personal computers and communication terminals, and electric vehicles.

[0175] Explanation of symbols

[0176] 1 Storage element

[0177] 2 Electrode body

[0178] 3 Container

[0179] 4 Positive terminal

[0180] 41 Positive wire

[0181] 5 Negative terminal

[0182] 51 Negative lead

[0183] 20 Storage unit

[0184] 30 Power storage device

Claims

1. A storage element comprising an electrode body, wherein a positive electrode having a positive electrode active material layer and a negative electrode having a negative electrode active material layer are stacked with a separator interposed therebetween, The positive electrode active material layer contains positive electrode active material particles, and the internal porosity of the positive electrode active material particles is 15% or less. The negative electrode active material layer contains graphite particles, and the internal porosity of the graphite particles is 2% or less.

2. The electric storage element according to claim 1, wherein The positive electrode active material particles are secondary particles.

3. The electric storage element according to claim 1 or 2, wherein: The positive electrode active material particles include a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure.

4. The electric storage element according to claim 1 or 2, wherein: At least a portion of the electrode body is in a pressed state.

Citation Information

Patent Citations

  • Negative pole material for lithium battery, and lithium battery

    JP2005222933A

  • Negative electrode for power storage device, and power storage device

    JP2017069039A